Analysis of the Soil Microbiome of a Los Angeles Urban Farm - Savanah St. Clair; Maryam Saraylou; Daila Melendez; Norman Senn; Serina Reitz; Destini Kananipour; Angelo Alvarez (Applied and Environmental Soil Science)
This research aimed to address health and food security challenges affecting Los Angeles and beyond in our own backyard. One possible way to combat these challenges is through biotechnology. The purpose of this research was to characterize the arable soils at Los Angeles Pierce College and their potential uses. The methods employed were collection of soil physical and chemical properties, cultivation of soil microorganisms, and 16S rDNA sequencing with a citizen science platform. Statistical analysis in R revealed associations between field conditions and life in the soil. The testing of plant-based antimicrobial agents on antibiotic-resistant bacteria revealed that plant oils could be more efficacious for control than common antibiotics. We found evidence of plant growth-promoting, antibiotic-producing, and bioremediating bacteria in different fields with distinct microclimates based on the 16S rDNA taxonomy results and inferred functional profiles. The major findings included an abundance of Streptomyces, Bacillus, Methylobacteria, and others with desirable functions. Numerous Streptomyces isolates cultivated on selective media demonstrated the ability to reduce nitrate. These results will empower future trials and product development by identifying target soil microorganisms and the most viable fields.